Gap Analysis of Spiritual Education Provision for Hospitalized Patients: Integrating Health Promotion in Hospital Settings - Muhammad Syahwal; Arfiyan Sukmadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Spiritual health is an important component of holistic healthcare that influences clinical outcomes and patient recovery processes. In the PRECEDE–PROCEED health promotion model, the fulfillment of spiritual needs is influenced by predisposing, facilitating, and reinforcing factors. There is still a significant gap between patients' spiritual needs and the services provided, especially in relation to worship guidance and strengthening relationships with God during treatment. To analyze the discrepancy between expected and provided spiritual education interventions for inpatients through the lens of health promotion. Methods: We conducted a quantitative descriptive study in a private hospital in Kendari City in June-July 2025. The participants were 76 inpatients (aged ?18 years with a minimum stay of 2 days) and 15 nurses (clinical experience ?6 months), who were recruited through purposive sampling. Data collection used a validated structured questionnaire with acceptable internal consistency (Cronbach's Alpha ?0.70). Descriptive analysis was performed using jamovi software, while the gap between expected and provided education was analyzed through percentage comparisons and unmet need ratio calculations. Results: A significant discrepancy was found between patients' expectations of spiritual education and nursing practices. Only 9.2% of patients received education on strengthening spiritual connections, while 31.5% reported needing this support. Guidance on adjusting worship practices was provided to only 3.4% of patients, even though 12.7% expressed this need. Interestingly, 67.1% of patients continued their worship during illness, yet 88.2% of nurses did not offer guidance on worship adjustments. Conversely, over 85.5% of nurses provided education on patience, while only 29.8% of patients needed it. Major barriers included sensitivity to spiritual topics, limited time, and inadequate spiritual knowledge. Conclusion: The significant gap between expectations and services indicates systemic weaknesses in competency, support, and care orientation. Comprehensive and multilevel interventions are essential to ensure the accommodation of spiritual care in nursing services.